Methodological Approaches To Designing A System For Developing Geographical Culture - Matsaidova Sayyora Khudayberganovna (Zien Journals, 2026)
This article examines the theoretical and methodological foundations for developing a methodological system aimed at forming geographical culture in future geography teachers. Geographical culture is interpreted as an integrative set of an individual’s spatial thinking, territorial responsibility, environmental awareness, digital literacy, and professional competencies. The study scientifically substantiates the role of competency-based, systemic, activity-oriented, learner-centered, integrative, and information and communication technology (ICT) approaches within the methodological system. The target, content, technological, and diagnostic components of the methodological system are identified, and their interrelationships are revealed. The research findings contribute to the modernization of the process of training geography teachers.
Keywords: geographical culture; methodological system; competencies